Smartphone dalam Konstruk Teori Ikhlas Beribadah di Era Revolusi Industri 4.0 - Lutfiyah, Lutfiyah (FIKRAH, 2019)
Digital era, smartphone gives birth to a new culture for its users. The news is true and the hoax is going back and forth on social media. The religious behavior between the servant and his Lord should be private and not become a private matter with evidence of the display of ritual worship on social media. Worship should be performed specifically and privately, starting to be displayed through a smartphone and can be consumed by the general public. The purpose of this research is to determine the function of a smartphone when it is clashed with the theory of sincere worship during the Industrial Revolution 4.0 era. This paper uses a closed interview technique with a questionnaire, and documentation to reveal how the theory of worship should be carried out, the sincere theory that has been defined by the salaf scholars and how the translation of Muslims in the digital age. The subject of this paper is a lecturer in Islamic Education (PAI) at the Walisongo State Islamic University (UIN) Semarang. The results of this paper indicate that PAI lecturers actively use smartphones, but do not pay attention to the content of the post ofworship mahdhah with more evidence of abstention.